n Ondersoek na aspekte rakende die ontkiemingsfisiologie van Augea capensis Thunb. - Van der Merwe, Carel Andreas (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Sc.) -- Universiteit van Stellenbosch, 1991.